Predictive factors for short-term visual outcome after intravitreal triamcinolone acetonide injection for diabetic macular oedema: an optical coherence tomography study. Issue 6 (15th November 2006) - Brasil, Oswaldo Ferreira Moura; Smith, Scott D; Galor, Anat; Lowder, Careen Y; Sears, Jonathan E; Kaiser, Peter K
Abstract : Aim: To evaluate the predictive factors for visual outcome after intravitreal triamcinolone acetonide injection to treat refractory diabetic macular oedema (DME). Methods: A retrospective chart review of patients with DME who met the following inclusion criteria was performed: clinically significant diabetic macular oedema, receipt of a 4 mg/0.1 ml intravitreal triamcinolone acetonide injection and an optical coherence tomography (OCT) of the macula performed up to 10 days before injection. All patients received a full ophthalmic examination including best-corrected Snellen visual acuity (VA). The main outcome measure was the mean change in vision 3 months after injection. Results: Data from 73 eyes of 59 patients were analysed. After a mean follow-up of 324 days, the mean change in vision was −0.075 logarithm of minimum angle of resolution (logMAR) units, with 27.3% improving ⩾3 lines, 6.8% declining ⩾3 lines and 60.2% remaining stable within 1 line of baseline vision. Statistical analysis was performed using multivariate generalised estimating equations on the basis of data from 52 eyes of 42 patients. Factors associated with an improvement in vision 3 months after injection were worse baseline VA (−0.27 logMAR units/unit increase in baseline VA, p = 0.002) and presence of subretinal fluid (−0.17 logMAR units, p = 0.06). The presence of cystoid macular oedema negatively affected the visual outcome (0.15 logMAR units, p = 0.03). In addition, the presence of an epiretinal membrane (ERM) was associated with less visual improvement. ERM modified the effect of baseline VA as demonstrated by a significant interaction between these two variables (0.34 logMAR units/unit increase in baseline VA, p = 0.04). Conclusions: OCT factors and baseline VA can be useful in predicting the outcomes of VA 3 months after intravitreal triamcinolone acetonide injection in patients with refractory DME.